EARLY LEARNING AND CHILD CARE FOR IMMIGRANT FAMILIES AND CHILDREN: A PAN-CANADIAN JURISDICTIONAL SCAN OF SETTLEMENT AGENCIES - Fakhari, Nahal; Pimentel, Milena; McIsaac, Jessie-Lee D. (International Journal of Child, Youth and Family Studies, 2025)
High-quality early learning and child care programs are in a position to support immigrant family settlement, reduce socioeconomic inequities, and enhance children’s overall development. In Canada, these can be delivered either as provincially or territorially licensed programs or through settlement agencies. The goal of this research was to understand what factors influence the implementation of child care in settlement agencies across Canada. We conducted an environmental scan of settlement agencies and invited key informants to participate in interviews and surveys. Overall, the 38 participating organizations identified factors influencing the successful implementation of child care delivery at settlement agencies at both the system level (licensing and regulation, funding, workforce changes) and operational level (enhanced access to child care, cultural and linguistic diversity of educators). The findings also suggest a need to continue to emphasize broader purposes for early learning and child care programs, such as providing support to the whole family by allowing parents to access other services such as language training and information classes. Strategic connections between settlement agencies and provincially or territorially licensed programs will contribute to the professionalization of the field and to greater access to child care for immigrant families across the country.